Konten Hadis di Media Sosial: Studi Content Analysis dalam Jejaring Sosial pada Akun Lughoty.com, @RisalahMuslimID, dan @thesunnah_path - Maulana Wahyu Saefudin; Agus Suyadi Raharusun; Muhamad Dede Rodliyana (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the fact that the forms of hadith content that are spread on Lughoty.com, @RisalahMuslimID, and @thesunnah_path accounts are not always complete in the structure of a hadith and are not always considered authentic. This study aims to discuss the content of hadith on social media in social networks Facebook, Twitter, and Instagram with the sample accounts Lughoty.com, @RisalahMuslimID, and @thesunnah_path. This research is a qualitative type through a literature study that analyzes hadith content on social media using content analysis methods. The results and discussion of this study are an understanding of contextualization of hadith in the 21st century with technological advances in the information sector, and the form of hadith content on Lughoty.com, @RisalahMuslimID, and @thesunnah_path accounts does not always have a complete structure in a hadith. This study concludes that the hadith content found on social media in the Facebook, Twitter, and Instagram social networks on the Lughoty.com, @RisalahMuslimID, and @thesunnah_path accounts are not always judged to be authentic or hasan nor are all hadiths found on social networks. have completeness so that it is necessary to re-examine the obtained hadith to find the truth about the quality of a hadith.